A high‐confidence reference dataset of differentially expressed proteins in elongating cotton fiber cells. Issue 7 (25th February 2013) - Zhang, Bing; Yang, Yi‐Wei; Zhang, Yu; Liu, Jin‐Yuan
<x xml:space="preserve">Abstract</x> In our previous study, we used a comparative proteomic approach based on 2DE to profile dynamic proteomes of cotton fibers and found 235 protein spots differentially expressed during the elongation process ranging from 5 to 25 days post‐anthesis. Of them, only 106 differentially expressed proteins (DEPs) were identified by MS due to database limitations at the time. In the present work, we successfully identified the remaining 129 DEPs from the same experimental system using high‐resolution MS with an updated database. Bioinformatic analysis revealed that proteins involved in carbohydrate and protein metabolism, transport, and redox homeostasis are the most abundant, and glycolysis was found to be the most significantly regulated process during fiber elongation. Our high‐confidence reference dataset, composed of 235 DEPs, provides a valuable resource for future studies on the molecular mechanism of cotton fiber elongation.